2003
DOI: 10.1136/sti.79.4.301
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of genitourinary medicine clinic attenders provides little evidence of sexual transmission of hepatitis C virus infection

Abstract: Objective: To determine the prevalence and genetic diversity of hepatitis C virus in genitourinary medicine clinic attenders and to assess the extent of sexual transmission of the virus. Methods: A cross sectional, unlinked, anonymous survey in 14 genitourinary medicine clinics situated in England, Wales, and Northern Ireland. Serum specimens from genitourinary medicine clinic attenders, retained as part of the Unlinked Anonymous Prevalence Monitoring Programme (UAPMP) serum archive, were tested in small pools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 31 publications
4
28
0
Order By: Relevance
“…The incidence among those tested was also low, and was comparable with recent estimates of hepatitis C incidence in low-risk populations 11 12. The characteristics of anti-HCV-positive individuals described here confirm previous reports that suggest anti-HCV positivity is higher in males and in IDU 13 14. One limitation of this study was the paucity of information on risk factors, with our sources limited to a freetext clinical details field.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence among those tested was also low, and was comparable with recent estimates of hepatitis C incidence in low-risk populations 11 12. The characteristics of anti-HCV-positive individuals described here confirm previous reports that suggest anti-HCV positivity is higher in males and in IDU 13 14. One limitation of this study was the paucity of information on risk factors, with our sources limited to a freetext clinical details field.…”
Section: Discussionsupporting
confidence: 86%
“…18 A larger, more recent study in genitourinary clinics in the United Kingdom, using similar methods, found a low prevalence of anti-HCV among non-IDU, with the anti-HCV prevalence in MSM not significantly different from non-MSM (0.92% vs. 0.75%, PR 1.23; 95% CI 0.76, 1.98). 19 The prevalence of HCV infection among MSM in STD clinics has generally been found to be no higher than among heterosexuals. [6][7][8] Only one study of STD clinic clients found male homosexual activity to be an independent risk factor for HCV infection, but this association became nonsignificant when HIV infection was included in the multivariate model.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy for most genotypes remains low, however, with specific problems in HIV-positive individuals 6 – 8. The main risk factor in the United Kingdom is injecting drug use 9 10. Historically, using data from heterosexual HCV discordant couples, the risk of sexual transmission was considered to be low.…”
mentioning
confidence: 99%